ANALISIS PERSEPSI NASABAH DAN PERKEMBANGAN UMKM SETELAH MEMPEROLEH PEMBIAYAAN MUDHARABAH (Studi Kasus BPRS Binama Kota Semarang) - Siti Barokah; Ayu Noviani Hanum (Universitas Muhammadiyah Semarang, 2013)
The purpose of this study was to analyze the perception and development of Micro, Small and Medium Enterprises between before and after obtaining the financing mudharabah of BPRS Binama Semarang City, viewed from the side of working capital, profits, employment and profits.Data that used is simple random sampling on the BPRS Binama. Of the population of 100 respondents, 50 respondents of samples used. Type of test used is a validity test, reliability test, and the sign rank test Wilxocon. Experiments were done using SPSS PASW 18 program.Based on research results of the descriptive analysis of the overall submission process until the liquefaction process, customers expressed easily in obtaining financing. From the test results the insignia wilxocon there is developmental differences the UMKM between before and after financing of mudharobah with details of the amount of working capital increased by 165%, turnover increased by 79%, total employment increased 33% and profits by 82%. Keywords: Perception, Financing Mudharabah, UMKM